Descriptive Analysis Regarding Optic Canal Variations: A Study In South Punjab Region Of Pakistan - Mirani, Ponum; Rasheed, Ammara; Afshan, Gul; Rasheed, Nida (Journal of Rawalpindi Medical College, 2024)
Objective: This study aimed to conduct a comprehensive investigation into optic canal variations within the South Punjab region of Pakistan. The primary objectives were to analyze the size, shape, and anomalies of the optic canal, providing valuable insights for healthcare professionals and researchers involved in ophthalmology, neurosurgery, and radiology. Methods: A meticulous examination of 221 dried cadaveric human skulls from Nishtar Medical University’s Anatomy Department was undertaken. The sample was carefully selected to ensure diverse representation across age groups and genders, contributing to a robust dataset for analysis. Optic canal dimensions were measured using precision callipers and digital devices, encompassing length, width, and height. Qualitative analyses involved scrutinizing variations in shape, such as curvature, tapering, and irregularities. Specific anomalies, including optic canal duplication, were identified and documented. Ethical guidelines were strictly followed with approval from the institutional review board (IRB). Statistical analyses, conducted using SPSS 22.0, included measures like mean, median, and standard deviation, providing a rigorous framework for discerning patterns and variations within the optic canal. Results: The study revealed significant anatomical variations within the optic canal. Quantitative analysis of size variations demonstrated mean lengths, widths, and heights, offering insights into the normative anatomy of the optic canal in the South Punjab population. Diverse shapes were observed, with the majority displaying a gently curved configuration. Anomalies, including optic canal duplication and the keyhole anomaly, were identified, contributing to our understanding of rare anatomical peculiarities. Slight but noteworthy differences between the right and left optic canals were observed, with the right side generally displaying larger dimensions and specific anomalies. Conclusion: The findings contribute valuable insights into optic canal morphology, emphasizing its complexity and diversity within the South Punjab population. These results hold practical implications for clinicians, informing diagnostic imaging, surgical planning, and interventions involving the optic canal. The study underscores the importance of individualized patient care, considering the variations in optic canal anatomy. As our understanding advances, these findings pave the way for enhanced clinical assessments and nuanced approaches to cranial anatomical considerations, ultimately improving patient outcomes and guiding future research in this field.